PENINGKATAN KONSENTRASI BELAJAR MELALUI SENAM ANAK INDONESIA HEBAT (SAIH) PADA SISWA SD NEGERI 36 BANDA ACEH - Zahratul Ulya; Intan Kemala Sari; Irwandi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Learning concentration is an essential ability that students must possess to support the success of the learning process, yet many students at SD Negeri 36 Banda Aceh still exhibit low focus during lessons. This study aims to determine the improvement of students' learning concentration through the Senam Anak Indonesia Hebat (SAIH) program. The research employed a quantitative approach with an experimental method, specifically a one-group pretest-posttest design. The population consisted of 186 students, and a sample of 29 fifth-grade students was selected using purposive sampling. Data were collected through observation, Likert-scale questionnaires, and documentation, then analyzed using mean, standard deviation, and t-test calculations. The results of the study indicate that there is a significant effect of the SAIH program on students' learning concentration. This is supported by the t-calculated value of 10.18, which is higher than the t-table value of 1.70 at a significance level of 0.05. Furthermore, the average concentration score increased from 34.13 in the pretest to 38.86 in the posttest. It is concluded that the implementation of SAIH effectively enhances student focus and readiness in the classroom.